A primeira impressão é a que fica: pandemia da covid-19 e a leitura visual nos jornais O Imparcial e O Estado do Maranhão - SANTOS, Tamara Cristina Bastos (2021)
The year 2020 presented a scenario that offers a stock of creative covers. This is the case of São Luís, where O Imparcial and O Estado do Maranhão are vehicles that come, with a certain frequency, using the option for poster covers, or poster covers, for viewing the first pages, especially in this pandemic period. . In this way, this work used 6 covers referring to this context, 3 from Imparcial and 3 from O Estado, combining these analyzes with the theoretical references of the visual field, together with the grammaticalities available about a possible visual language syntax and the assumptions that guide the studies that have as points of view documents of the artistic creation process. It was perceived in this corpus an interdisciplinary perspective that demonstrated the trajectory of visuality in contents beyond journalism, as is the case of poetry, concrete art and the multidimensions that permeate the way these vehicles from Maranhão used creativity to inform and transmit sensations.